Functionally Decorated Carbon Nanotube Networks for Energy Storage in Supercapacitors - Nawwar, Mohamed; Sahu, Rakesh P.; Puri, Ishwar K.; Zhitomirsky, Igor (Frontiers in Energy Research, 2020)
A novel approach has been developed for the fabrication of Fe3O4 decorated multiwalled carbon nanotubes (MWCNT) for energy storage in negative electrodes of electrochemical supercapacitors. Synthesis of Fe3O4 was performed in the presence of MWCNT, dispersed using various cationic and anionic polyaromatic dispersants. The comparison of experimental results obtained using different dispersants provided an insight into the influence of the chemical structure of the dispersant molecules on the microstructure of the Fe3O4-MWCNT materials. It was found that positively charged groups and chelating catechol ligands of the dispersants facilitated the formation of Fe3O4 decorated MWCNT with low agglomeration. The Fe3O4 -MWCNT materials, prepared using different dispersants were used for the fabrication of electrodes with mass loading of 40 mg cm−2. The highest capacitance was obtained in 0.5 M Na2SO4 electrolyte for Fe3O4 decorated MWCNT prepared using cationic celestine blue dye as a dispersant. Improved cyclic voltammetry profile was obtained using FeOOH as an additive. Asymmetric devices were fabricated and tested based on the Fe3O4 decorated MWCNT negative electrodes and MnO2-MWCNT positive electrodes.